"When we were young" comparisons and correlates of negative childhood experiences - Bravo, Vivian F.
Negative childhood experiences in the forms of abuse, neglect, and household dysfunction are potentially traumatic events that have long-lasting impacts on individuals. Previous studies have shown that these experiences are linked to negative health outcomes such as health-risk behaviors, chronic diseases, and negative psychological outcomes. There was a rapid increase in studies that investigate negative childhood experiences worldwide but these were mostly saturated in high socioeconomic status (SES) populations. Several studies were conducted to investigate these experiences in poor countries but these were mostly situated abroad. To date, studies on negative childhood experiences that investigate their link to parental SES, current SES, and health outcomes are scarce in the Philippines. Apart from that, local studies that compare the occurrences of these experiences between different SES are also scant. Addressing these gaps, this study utilized respondents from low and middle SES to understand the link between negative childhood experiences, parental SES, current SES, and health outcomes in adulthood. Using descriptive and correlational methods, this study revealed that there are higher incidences of negative childhood experiences in low-SES compared to middle-SES, suggesting that abuse, neglect, and household dysfunction are more common in low SES and poor communities. Associations between these experiences, parental SES, current SES, and health outcomes are also found. More so, it reveals differing health outcomes in low- and middle-SES. The greater implications of these findings are discussed. The findings of this study support the need for prevention and intervention for negative childhood experiences.